A Corpus-Based Critical Discourse Analysis of ‘Chinese Model’ on Africa Mainstream Newspapers - Liu, Xin; Liu, Wenyu (Advances in Social Sciences Research Journal, 2019)
In recent years, China’s economy and international influence grows increasingly, “Chinese model”, China’s successful development experience, has been extensively discussed around the world. As friendship and communications between China and Africa becomes more osculation, Africa’s attitudes towards “Chinese model” matters much and cannot be ignored. In order to objectively and systematically examine African cognition and attitudes towards “Chinese model”, this research collects most of the news reports on “Chinese model” in African mainstream newspapers from 2000 to 2017. Assisted by corpus software, this paper conducts an analysis on Co-occurrence Network of Words around Chinese model, keywords of the texts, and concordance lines of Chinese model. Furthermore, semantic prosody will be explored in concordances. The findings suggest that: (1) On the discussion of Chinese model, the focus of African media is primarily on their economic development, China’s investment, trade and cooperation, and expectation to draw upon Chinese development experience to relieve them from poverty. (2) Most of the reports on Chinese model are strongly associated with economy, and only a few reports involves with politics. (3) On the point of replicating Chinese model in facilitating African development, the majority of Africans are affirmative of this approach. There are only a few reports in which people show their uncertainty and worries about the prospect of applying Chinese model in Africa.